The use of instructional videos and notes in teaching agricultural knowledge and skills: an experimental study at Universiti Putra Malaysia - Hassan, Md Salleh; Sanggun, Enisar (Universiti Putra Malaysia Press, 1997)
A quasi-experimental research study was conducted with first-year Diploma of Agriculture students to find out the effects of instructional multi-media on their knowledge and skills achievement during their fieldwork training at the farm. The students were divided into five groups of 30 students each, and each group was assigned a different treatment. The skill selected for the experiment was marcotting of guava (Psidiu1Il. guajava). The findings of the study show that an instructional video and notes are beneficial and effective to the students before they carry out their fieldwork training. Students who watched the instructional video had significantly higher knowledge than the students who did not watch the video. However, instructional notes did not have any significant effect. The results also show that an instructor trained in using multimedia had a significant effect on the students' skill in making the marcot.